KRITIK EKONOMI PANCASILA TERHADAP FENOMENA PENINGKATAN E-COMMERCE DI INDONESIA TAHUN 2020 - Wikantari, Maria Assumpta; Supriadi, Yudi Nur (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2021)
The purpose of this study is to find out the economic criticism of Pancasila against the phenomenon of increasing e-commerce in Indonesia in 2020. The research method used is a descriptive method with a type of qualitative research. The method used in this writing is library research,where the retrieval of primary and secondary data for the selection of data relevant to a large theme andanalyzed through a predetermined view. The results of this study show that the Pancasila economy is experiencing difficulties as a whole, and must compete with the pace of market, demand, and supply. E-commerce media is a bridge between buyers and sellers, but has difficulty fulfilling the wishes of sellers. the use of e-commerce as a liaison between buyers and sellers, internet access can make the market wider. Not only at the national level, but at the international level through Indonesia's human resources which is more responsive, resilient, with global skills